2013
DOI: 10.1128/jcm.03371-12
|View full text |Cite
|
Sign up to set email alerts
|

Serum Arginase, a Biomarker of Treatment Efficacy in Human African Trypanosomiasis

Abstract: g Arginase serum levels were increased in human African trypanosomiasis patients and returned to control values after treatment. Arginase hydrolyzes L-arginine to L-ornithine, which is essential for parasite growth. Moreover, L-arginine depletion impairs immune functions. Arginase may be considered as a biomarker for treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Meanwhile, there are some studies that have reported higher levels of arginase and polyamines (arginase products) in the sera and tissues of breast cancer patients [ 28 ]. Increased arginase activity probably causes damage to the host's immune response [ 29 ]. In our study, the arginase activity in the tissues of normal mice was significantly lower than in the therapeutic and control groups ( Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, there are some studies that have reported higher levels of arginase and polyamines (arginase products) in the sera and tissues of breast cancer patients [ 28 ]. Increased arginase activity probably causes damage to the host's immune response [ 29 ]. In our study, the arginase activity in the tissues of normal mice was significantly lower than in the therapeutic and control groups ( Figure 6B ).…”
Section: Discussionmentioning
confidence: 99%
“…In human African trypanosomiasis caused by Trypanosoma gambiense, arginase serum levels increase and return to control values after treatment (9). Accordingly, in experimental murine infection by Trypanosoma brucei, host macrophage arginase activity represents a marker of susceptibility to the disease (10).…”
mentioning
confidence: 99%
“…Furthermore, arginase has been linked with various diseases, including those affecting the central nervous system, kidneys, the cardiovascular system, as well as immune dysfunction and cancer [ 1 ]. The essential role of arginase and inducible L-arginine metabolism in infectious diseases has been demonstrated in experimental trypanosomiasis and leishmaniasis and has since emerged as playing an important role in infections such as human African trypanosomiasis (HAT), AIDS, malaria, human leishmaniasis and COVID-19 [ 2 5 ]. Arginase induction is the hallmark of the type 2 immune response and alternative activation of macrophages and is also a marker of myeloid-derived suppressor cell activity.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of arginase activity with the Corraliza (modified Schimke’s method) micromethod is one of the most commonly used methods. This micromethod was initially employed to evaluate arginase activity in macrophages from infected mice and then in sera from HAT patients, as a biomarker of treatment efficacy [ 2 , 9 ]. The conventional Corraliza micromethod requires 50 µl of sample, several transfers between different types of tubes, and various pieces of relatively large equipment such as a water bath, an incubator, an oven, and spectrophotometer, making this procedure relatively labor-intensive.…”
Section: Introductionmentioning
confidence: 99%